Causes of post-operative pain related to root canal treatment - Zawrzykraj, Ewa; Krużyński, Wiktor; Radwański, Mateusz; Łukomska-Szymańska, Monika (Journal of Stomatology, 2022)
Post-operative pain is a common complication during root canal treatment (RCT). Its’ prevalence ranges from 25% to 72% in the first 24 hours after treatment. There are several factors that affect post-operative pain occurrence. They are associated with the patient, canal preparation technique, and parameters of applied files. The apical foramen widening and apical extrusion of debris are the most important direct causes of post-operative pain. Clockwise or counterclockwise motion of the file may support the extraction of dentinal chips and extrusion of debris in the periapical area. Both incidence and intensity of pain are significantly lower after preparation with rotary instruments in comparison to reciprocating systems and hand files. Cross-section and taper of the instrument affect the amount of space for debris and efficiency of its’ removal. Moreover, reduction of cross-section area and number of cutting edges are advantageous. Preparation of the apical part of root canal determines the risk of physiological foramen transportation or widening (over-preparation), resulting in increased incidence of post-operative pain. There are significant discrepancies related to the number of visits on treatment and its’ influence on discussed ailment occurrence. Single-visit RCT provides both higher healing rate and more often discussed ailment occurrence than multi-visit one.